2014
DOI: 10.1017/s1368980014001256
|View full text |Cite
|
Sign up to set email alerts
|

Associations between parental feeding practices, problem food behaviours and dietary intake in New Zealand overweight children aged 4–8 years

Abstract: Objective: Parents report that children's eating behaviours are a major barrier to providing them with a healthy diet. Links between problem eating behaviours and parental feeding practices are not well established and have not previously been examined in overweight children. The aim of the present study was to assess associations between problem food behaviours, dietary intake and parental feeding practices of overweight children aged 4-8 years. Design: Participants were recruited for a lifestyle intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
2
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(80 citation statements)
references
References 30 publications
(57 reference statements)
7
63
2
5
Order By: Relevance
“…Lifestyle Behaviour Checklist (West & Sanders, 2009) Five items including refusal to eat foods and resistance or difficult behaviour around food Haszard et al (2014) Children's Eating Behaviour Questionnaire (Wardle et al, 2001) Six items identified pickiness: high fussiness/high slowness in eating/high satiety responsiveness/low food enjoyment/low food responsiveness Bucher, Siegrist, and van der Horst (Baughcum et al, 2001) Six items on child being a picky eater (picky eating/willingness to eat new foods/has to have special food because picky/struggle to get to eat/poor appetite) Evans et al (2011) Oregon Research Institute Child Eating Behavior Inventory (Archer, Rosenbaum, & Streiner, 1991) Four items related to picky eating (food neophobia/food rejection/food preparation preferences/limited variety) Shim et al (2011) Four items identified pickiness: limited variety/food refusal/struggle for control/positive parental behaviour Lewinsohn et al (2005) Modified Pelchat and Pliner Questionnaire (Pelchat & Pliner, 1986) tasted before' (from the Fussiness subscale of the CEBQ)). Studyspecific question(s) can be specially designed for the particular study cohort and can provide more flexibility than pre-existing questionnaire items.…”
Section: Measure Used To Assess Picky Eating Comment Authorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lifestyle Behaviour Checklist (West & Sanders, 2009) Five items including refusal to eat foods and resistance or difficult behaviour around food Haszard et al (2014) Children's Eating Behaviour Questionnaire (Wardle et al, 2001) Six items identified pickiness: high fussiness/high slowness in eating/high satiety responsiveness/low food enjoyment/low food responsiveness Bucher, Siegrist, and van der Horst (Baughcum et al, 2001) Six items on child being a picky eater (picky eating/willingness to eat new foods/has to have special food because picky/struggle to get to eat/poor appetite) Evans et al (2011) Oregon Research Institute Child Eating Behavior Inventory (Archer, Rosenbaum, & Streiner, 1991) Four items related to picky eating (food neophobia/food rejection/food preparation preferences/limited variety) Shim et al (2011) Four items identified pickiness: limited variety/food refusal/struggle for control/positive parental behaviour Lewinsohn et al (2005) Modified Pelchat and Pliner Questionnaire (Pelchat & Pliner, 1986) tasted before' (from the Fussiness subscale of the CEBQ)). Studyspecific question(s) can be specially designed for the particular study cohort and can provide more flexibility than pre-existing questionnaire items.…”
Section: Measure Used To Assess Picky Eating Comment Authorsmentioning
confidence: 99%
“…Other questionnaires such as the Lifestyle Behaviour Checklist (West & Sanders, 2009) (e.g. Haszard et al (2014)) and the Child Behaviour Checklist (Richman & Graham, 1971) (e.g. Cardona Cano et al, 2015;Hafstad et al, 2013) are also in recent use, as are studyspecific measures (e.g.…”
Section: Measure Used To Assess Picky Eating Comment Authorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although monitoring can be viewed as an authoritative and positive feeding practice in relation to children's intake of high-energy dense foods and excessive weight gain (Brown & Ogden, 2004;Faith, Scanlon, Birch, Francis, & Sherry, 2004;Haszard, Skidmore, Williams, & Taylor, 2014), our findings suggest that monitoring may negatively influence children's body esteem, especially among girls. In our sample, greater maternal monitoring was not only associated with lower body esteem in girls compared to boys, but its influence was substantially greater among overweight and obese girls.…”
Section: Discussionmentioning
confidence: 70%
“…Relación entre las prácticas alimentarias parentales con los retos y las problemáticas de la conducta alimentaria infantil reportadas en la literatura. Control del niño 4-8 Haszard et al (2015) también puede ser encubierta, cuando se limitan las oportunidades para consumir o la disponibilidad de alimentos en el hogar, sin mediar una restricción explícita; no obstante, sus efectos han sido poco estuUna posible solución a esto sería identificar la distinción entre las conductas con una terminología diferente, o bien, realizar subcategorías de las PAP. Ogden, Reynolds y Smith (2006) Notas.…”
Section: Razonamientounclassified